Green Synthesis & Biological Evaluation of Novel Benzimidazole Derivatives as Antianxiety Agents (Journal of Basic and Applied Research in Biomedicine, 2022)
Benzimidazole is one of the most important heterocyclic compound, having varied biological activities and still of great scientific interest now a days. They are widely found in bioorganic and medicinal chemistry with application in drug discovery. In the present study some novel benzimidazole derivatives were synthesized under green synthesis by solvent free conditions by using catalytic amount of silica supported sodium hydrogen sulphate according to the scheme. All the synthesized benzimidazole derivatives have been characterized by using elemental analysis, FT-IR, 1HNMR, 13C NMR spectroscopy and further supported by Mass spectroscopy. Purity of all the compounds has been checked on thin layer chromatographic plate and HPLC technique. All the synthesized compounds were tested for their anti anxiety and neurotoxicity activities by elevated plus maze test in mice. Test compounds and diazepam was administered intraperitoneally in antianxiety study at dose of 2 mg/kg. Compounds BZ-6 & BZ-7 showed highest antianxiety activity compared to diazepam and did not show neurotoxicity in rotarod test. All the compounds exhibited moderate to significant antianxiety activity.